Impact of rapid antigen detection testing on antibiotic prescription in acute pharyngitis in adults. FARINGOCAT STUDY: a multicentric randomized controlled trial - Madurell, Jordi (BioMed Central, 2010)
BACKGROUND: Acute pharyngitis is one of the most frequent consultations to the general practitioner and in most of the cases an antibiotic is prescribed in primary care in Spain. Bacterial etiology, mainly by group A beta-hemolytic streptococcus (GABHS), accounts for 10-20% of all these infections in adults. The purpose of this study is to assess the impact of rapid antigen detection testing (RADT) to identify GABHS in acute pharyngitis on the utilization of antibiotics in primary care. METHODS/DESIGN: Multicentric randomized controlled trial in which antibiotic prescription between two groups of patients with acute pharyngitis will be compared. The trial will include two arms, a control and an intervention group in which RADT will be performed. The primary outcome measure will be the proportion of inappropriate antibiotic prescription in each group. Two hundred seventy-six patients are required to detect a reduction in antibiotic prescription from 85% in the control group to 75% in the intervention group with a power of 90% and a level of significance of 5%. Secondary outcome measures will be specific antibiotic treatment, antibiotic resistance rates, secondary effects, days without working, medical visits during the first month and patient satisfaction. DISCUSSION: The implementation of RADT would allow a more rational use of antibiotics and would prevent adverse effects of antibiotics, emergence of antibiotic resistance and the growth of inefficient health expenses. TRIAL REGISTRATION: ISRCTN23587778